Engineering the Rhizosphere. (March 2016) - Dessaux, Yves; Grandclément, Catherine; Faure, Denis
Abstract : All components of the rhizosphere can be engineered to promote plant health and growth, two features that strongly depend upon the interactions of living organisms with their environment. This review describes the progress in plant and microbial molecular genetics and ecology that has led to a wealth of potential applications. Recent efforts especially deal with the plant defense machinery that is instrumental in engineering plant resistance to biotic stresses. Another approach involves microbial population engineering rather than single strain engineering. More generally, the plants (and the associated microbes) are no longer seen as 'individual' but rather as a holobiont, in other words a unit of selection in evolution, a concept that holds great promise for future plant breeding programs. Trends: All components of the rhizosphere (plants and microbes) can be engineered and soil can be amended to promote plant health and growth, from the field to the landscape scale. Plant engineering has led to valuable results in terms of resistance to high metal concentration in soil and resistance to pathogens, in this latter case in relation with remarkable progress in the understanding of plant defense reactions. Aside from plant growth promoting rhizobacteria living at the root surface, endophytic bacteria are receiving renewed attention because they have proved to be of interest particularly in the context of tolerance to pollutants. A novel aspect of microbial engineering involves population engineering rather than single strain engineering. In relation to what is observed in the animal world, the vision of the plant and its associated microbial cortege is changing; they are not separate elements but rather constituents of a superorganism, the holobiont.